1998
DOI: 10.1159/000026493
|View full text |Cite
|
Sign up to set email alerts
|

Platelet 5-HT and Plasma Cortisol Concentrations after Dexamethasone Suppression Test in Patients with Different Time Course of Schizophrenia

Abstract: Platelet 5-HT and plasma cortisol concentrations were determined in 59 schizophrenic patients with different time course of illness before and after dexamethasone suppression test (DST). An abnormal DST (nonsuppression) was observed in 51% of patients. In these patients basal cortisol and platelet 5-HT concentrations were higher than in patients with normal DST. After DST, plasma cortisol levels were higher in nonsuppressors with intermittent and intermittent-chronic time course, whereas platelet 5-HT concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…hypercortisolemia). Altered HPA axis activity—particularly hypercortisolemia—is one of the most consistently observed pathophysiologies in MDD patients (Gibbons and Mc, 1962) and is observed in both BP and SZ (Altamura et al, 1999, Daban et al, 2005, Jakovljevic et al, 1998). As glucocorticoids exert powerful transcriptional effects through the GR (with GR mRNA level significantly reduced in MDD versus control patients in a prior study (Qi et al, 2013)) and miR-34a exerts influence over a GR cofactor, these findings suggest a role for miR-34a in the transcriptional response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…hypercortisolemia). Altered HPA axis activity—particularly hypercortisolemia—is one of the most consistently observed pathophysiologies in MDD patients (Gibbons and Mc, 1962) and is observed in both BP and SZ (Altamura et al, 1999, Daban et al, 2005, Jakovljevic et al, 1998). As glucocorticoids exert powerful transcriptional effects through the GR (with GR mRNA level significantly reduced in MDD versus control patients in a prior study (Qi et al, 2013)) and miR-34a exerts influence over a GR cofactor, these findings suggest a role for miR-34a in the transcriptional response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated cortisol levels (Lerer et al 1988; Monteleone et al 1992Monteleone et al , 1999Ryan et al 2003) and pathological dexamethasone suppression test results (Lammers et al 1995;Jakovljevic et al 1998) have repeatedly been found in patients suffering from schizophrenia. Furthermore, plasma levels of ACTH and cortisol in schizophrenic patients correlate positively with negative symptomatology (Shirayama et al 2002) and negatively with cognitive performance in a larger group of patients and controls (Walder et al 2000).…”
Section: Introductionmentioning
confidence: 91%
“…Hypothalamic-pituitary-adrenal (HPA) axis dysfunction is a frequent finding in different psychiatric disorders, including psychotic depression and schizophrenia (Lammers et al 1995;Jakovljevic et al 1998;Holsboer 2000;Meltzer et al 2001). Elevated cortisol levels (Lerer et al 1988; Monteleone et al 1992Monteleone et al , 1999Ryan et al 2003) and pathological dexamethasone suppression test results (Lammers et al 1995;Jakovljevic et al 1998) have repeatedly been found in patients suffering from schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated cortisol concentrations and dexamethasone nonsuppression have also been consistently found in patients suffering from schizophrenia [7][8][9]. Furthermore, plasma concentrations of ACTH and cortisol correlate positively with negative symptomatology in schizophrenic patients [10,11] and negatively with cognitive performance in a larger group of patients and controls [12].…”
Section: Introductionmentioning
confidence: 91%